Circulating resistin levels and mutation burden of the RETN gene variants predict long-term mortality in a Taiwanese population - Lung-An Hsu; Ming-Sheng Teng; Semon Wu; Mei-Siou Liao; Hsin-Hua Chou; Yu-Lin Ko (Scientific Reports)
Abstract Human resistin is a proinflammatory cytokine involving the development and progression of cancer and cardiovascular diseases. However, prediction of long-term outcome using circulating resistin level and its genetic determinants in a population-based study remain to be explored. After genome-wide association study (GWAS), DNA methylation (DNAm) analysis and functional assays of a RETN rs370006313 variant, we tested whether resistin level and its genetic determinants can be used to determine the long-term outcomes of 5678 Taiwan Biobank (TWB) participants. GWAS and DNAm analysis revealed RETN variants, rs3219175, rs370006313, and rs3745368, and DNAm sites, cg21271423 and cg09909011, independently associated with circulating resistin levels. Functional assays showed rs370006313 variant played a key role in affecting RETN promoter activity, whereas genotypes of rs3219175 and rs3745368, but not rs370006313, exhibited genome-wide significant associations with RETN promoter DNAm levels. Using Kaplan-Meier survival and Cox regression analyses, participants with progressively increasing resistin levels had a higher hazard ratio for all-cause mortality and cancer mortality compared to those with lower resistin levels. Participants with all three RETN variants (high mutation burden) also exhibited significantly higher hazard ratios for all-cause mortality and cancer mortality, at 3.99 and 5.55, respectively, compared to those without a high mutation burden. In conclusion, RETN rs370006313 is a functional variant affecting RETN promoter activity. Elevated circulating resistin levels and a high RETN mutation burden predict all-cause and cancer mortality in TWB participants. Both resistin levels and RETN variants may serve as biomarkers of long-term outcomes in the general Taiwanese populations.